Proposed multidimensional framework for understanding Chagas disease healthcare barriers in the United States. - Colin Forsyth; Sheba Meymandi; Ilan Moss; Jason Cone; Rachel Cohen; Carolina Batista (Public Library of Science (PLoS), 2019)
BACKGROUND:Chagas disease (CD) affects over 300,000 people in the United States, but fewer than 1% have been diagnosed and less than 0.3% have received etiological treatment. This is a significant public health concern because untreated CD can produce fatal complications. What factors prevent people with CD from accessing diagnosis and treatment in a nation with one of the world's most advanced healthcare systems? METHODOLOGY/PRINCIPAL FINDINGS:This analysis of barriers to diagnosis and treatment of CD in the US reflects the opinions of the authors more than a comprehensive discussion of all the available evidence. To enrich our description of barriers, we have conducted an exploratory literature review and cited the experience of the main US clinic providing treatment for CD. We list 34 barriers, which we group into four overlapping dimensions: systemic, comprising gaps in the public health system; structural, originating from political and economic inequalities; clinical, including toxicity of medications and diagnostic challenges; and psychosocial, encompassing fears and stigma. CONCLUSIONS:We propose this multidimensional framework both to explain the persistently low numbers of people with CD who are tested and treated and as a potential basis for organizing a public health response, but we encourage others to improve on our approach or develop alternative frameworks. We further argue that expanding access to diagnosis and treatment of CD in the US means asserting the rights of vulnerable populations to obtain timely, quality healthcare.